2005
DOI: 10.1111/j.1525-139x.2005.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Understanding the Malnutrition‐Inflammation‐Cachexia Syndrome in Chronic Kidney Disease Patients: What is Next?

Abstract: Several recent clinical trials using single modalities to correct the conventional cardiovascular risk factors in patients with chronic kidney disease (CKD) or to improve dialysis dose and techniques in maintenance dialysis patients have failed despite the high rate of cardiovascular mortality in these individuals. Protein-energy malnutrition and inflammation, two relatively common and concurrent conditions in CKD patients, have been implicated as the main cause of poor short-term survival in this population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
124
3
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(140 citation statements)
references
References 60 publications
7
124
3
6
Order By: Relevance
“…1,4,18 This is of concern because of the strong association between PEW and increased morbidity and mortality, 1,2 higher hospitalization rate, and worse quality of life. 18 Nutritional assessment aims at identifying the risks or causes of the nutritional status deterioration, helping with the specific therapy and determination of the nutritional needs of each nutrient. Knowing and properly characterizing the nutritional status of a population on dialysis is fundamental to treat and prevent the development and worsening of PEW, and to determine and assess the impact of dietary therapy on nutritional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,18 This is of concern because of the strong association between PEW and increased morbidity and mortality, 1,2 higher hospitalization rate, and worse quality of life. 18 Nutritional assessment aims at identifying the risks or causes of the nutritional status deterioration, helping with the specific therapy and determination of the nutritional needs of each nutrient. Knowing and properly characterizing the nutritional status of a population on dialysis is fundamental to treat and prevent the development and worsening of PEW, and to determine and assess the impact of dietary therapy on nutritional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,10 These observations have led to speculation that this reverse epidemiology 11 contributes to the disappointing clinical benefits of statin treatment in dialysis populations. 12 In this study of over 800,000 people without kidney failure, we examined the relation between LDL-C and hospitalization for myocardial infarction in strata defined by eGFR. Although higher levels of LDL-C were associated with higher risk for all three eGFR strata, the excess risk associated with markedly elevated LDL-C seemed largest for participants with baseline eGFR$90 ml/min per 1.73 m 2 and lowest for participants with eGFR=15-59.9 ml/min per 1.73 m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…[37] Also, it was suggested that a worsening of atherosclerotic cardiovascular disease is mostly related to malnutrition-inflammation cachexia syndrome, a condition in which homocysteine levels are low instead of high. [38] Caglar et al showed that silent myocardial ischemia detected by single photon emission computed tomography in patients undergoing hemodialysis had higher homocysteine levels. [39] Thus, the results for our patients does not fulfill the terms of traditional epidemiology and paradoxical reverse epidemiology of homocysteine.…”
Section: Discussionmentioning
confidence: 99%